Analysis of the Effects of Soil on the Seismic Energy Responses of an Equipment-Structure System via Substructure Shaking Table Testing - Lanfang Luo; Nan Jiang; Jihong Bi (Shock and Vibration, 2019)
This study investigated the real-time substructure shaking table testing (RTSSTT) of an equipment-structure-soil (ESS) system and the effects of soil on the seismic energy responses of the equipment-structure (ES) subsystem. First, the branch modal substructure approach was employed to derive the formulas needed for the RTSSTT of the ESS system. Then, individual equations for calculating the energy responses of the equipment and the structure were provided. The ES subsystem was adopted as the experimental substructure, whereas the reduced soil model was treated as the numerical substructure when the RTSSTT was performed on the ESS system. The effectiveness of the proposed testing method was demonstrated by comparing the test results with those of the integrated finite element analysis. The energy responses of the ES subsystem in the case of rigid ground (i.e., the ES system) were compared with those considering the effects of soil (i.e., the ESS system). The input energy responses of the ES subsystem were found to decrease significantly after taking the effects of soil into account. Differences due to the soil effects should be considered in the seismic design for the ES system.